Utilization of individual lecithins in intestinal lipoprotein formation in the rat. - G M Patton; S B Clark; J M Fasulo; S J Robins (The Journal of Clinical Investigation, 1984)
To determine the molecular species composition of lecithins of different nascent lipoproteins, high density lipoproteins (HDL), very low density lipoproteins (VLDL), and chylomicrons (CM) were isolated from the mesenteric lymph of rats. Lymph was collected at 0 degrees C with 5,5'-dithiobis-2-dinitrobenzoic acid added to inhibit lecithin-cholesterol acyl transferase. CM were separated by ultracentrifugation and HDL from VLDL by dextran SO4-MG+2 precipitation. Molecular species of lecithin were directly isolated by reverse phase high performance liquid chromatography. In fasted animals, the lecithin compositions of lymph HDL and VLDL were virtually the same and closely resembled the lecithin composition of intestinal mucosa. When bile lecithin was eliminated (by bile diversion), there was a marked change in lecithin composition of all lipoprotein and mucosal samples, which was most notable for a reduction in 16:0-species (which are predominant in bile) and a relative increase in the corresponding 18:0-species. Feeding unsaturated triglycerides (triolein, trilinolein, or a combination of triolein and trilinolein) also resulted in a change in HDL and VLDL lecithin composition. The effect was similar whether bile lecithin was present or eliminated and was notable for a reduction in 16:0-species, an increase in 18:0-species, and the emergence of large amounts of diunsaturated lecithins that corresponded to the fatty acid composition of the triglycerides fed (i.e., 18:1-18:1, 18:2-18:2, and 18:1-18:2 lecithins). When bile-diverted rats were infused via the duodenum with a mix of [14C]choline-labeled lecithins (isolated from the bile of other rats), the incorporation of infused lecithins into different lymph lipoproteins was distinctly different. Individual lecithins were incorporated to a variable extent into each lipoprotein. In fasted rats the specific activities of all major molecular species of lecithin were relatively greater in VLDL than HDL, indicating that HDL derived proportionately more of its lecithins from an endogenous pool than did VLDL. Feeding triolein changed the specific activities of more of the lecithin species of VLDL than of HDL. The specific activities of lecithins in CM were more similar to VLDL than to HDL after triolein feeding. Results thus indicate that, although the lecithins of different mesenteric lymph lipoproteins are similar and may be derived from membrane sites with the same lecithin composition, lecithins incorporated into different lipoproteins originate from different metabolic pools and/or by different mechanisms.